Signed, sealed, delivered - Mabius, Eric; Booth, Kristin; Lowe, Crystal ([United States] : [Hallmark], 2015)
The movie that started it all. "Signed, Sealed, Delivered," introduces a dedicated, quartet of civil servants in the Dead Letter Office of the U.S. Postal System who transform themselves into an elite team of lost-mail detectives. Their determination to deliver the seemingly undeliverable takes them out of the post office into an unpredictable world where letters and packages from the past save lives, solve crimes, reunite old loves, and change futures by arriving late, but always miraculously on time. The intrepid team is led by the charming and handsome, but idiosyncratic, Oliver (Eric Mabius) who still considers the stamped and mailed letter to be the gold standard of human communication. His hapless team of lost letter experts, free-spirited Rita (Crystal Lowe) and oddly-intuitive Norman (Geoff Gustafson), are thrown for a loop when a beautiful, no-nonsense technophile named Shane (Kristin Booth) is mistakenly transferred to their inner sanctum. Shane inspires the lovable crew to step up in a risky and unorthodox way, beginning with a chance to clear the name of a wrongfully accused man and reconnect him with the love of his life. Will this dead letter make the truth come alive?
Title and description based on prepublication data.
Starring Eric Mabius, Kristin Booth, Crystal Lowe.
Rating: not rated.
DVD, color, widescreen, NTSC.
English audio.
Keywords: United States Postal Service. -- Dead Parcel Branch; Postal service -- Employees; Conduct of life; Post office stations and branches -- Drama; Feature films